Implementasi Asas Keterbukaan Dalam Pembuatan PERPPU Nomor 2 Tahun 2022 Tentang Cipta Kerja (UU Omnibus Law) - Sari, Dita Indah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Job Creation Law ultimately gave rise to a statement that it did not fulfill the principle of openness in the law formation process. The replacement regulation, namely